Characterisation of the temperature-dependent M1 to R phase transition in W-doped VO2 nanorod aggregates by Rietveld refinement and theoretical modelling. Issue 15 (1st April 2020) - Miao, Lei; Peng, Ying; Wang, Dianhui; Liang, Jihui; Hu, Chaohao; Nishibori, Eiji; Sun, Lixian; Fisher, Craig A. J.; Tanemura, Sakae
Abstract : Synchrotron XRD Rietveld refinement is combined with first-principles calculations to probe the effect of W doping on the IMT mechanism in VO2 nanorods, providing insights into the connection between atomic-scale phenomena and macro-scale properties. Abstract : Understanding the mechanism of the insulator–metal transition (IMT) in VO2 is a necessary step in optimising this material's properties for a range of functional applications. Here, Rietveld refinement of synchrotron X-ray powder diffraction patterns is performed on thermochromic V1− x W x O2 (0.0 ≤ x ≤ 0.02) nanorod aggregates over the temperature range 100 ≤ T ≤ 400 K to examine the effect of doping on the structure and properties of the insulating monoclinic (M1 ) phase and metallic rutile (R) phase. Precise measurement of the lattice constants of the M1 and R phases enabled the onset ( T on ) and endset ( T end ) temperatures of the IMT to be determined accurately for different dopant levels. First-principles calculations reveal that the observed decrease in both T on and T end with increasing W content is a result of Peierls type V–O–V dimers being replaced by linear W–O–V dimers with a narrowing of the band gap. The results are interpreted in terms of the bandwidth-controlled Mott–Hubbard IMT model, providing a more detailed understanding of the underlying physical mechanisms driving the IMT as well as a guide to optimising properties of VO2 -based materials for specific applications.